Warszawska rzeźba pomnikowa podczas okupacji niemieckiej 1939-1945 - Wiśniewska, Paulina (Saeculum Christianum. Pismo Historyczne, 2020)
The article presents the fate of monumental sculpture in occupied Warsaw 1939-1945. The aim of the Third Reich’s cultural policy adopted in Poland was to get rid of all traces of the Poles' cultural identity. This was manifest, i.a., in the destruction of Polish monuments. Therefore, it want to dispose of Polish monuments from the capital as objects that played a special role in maintaining the spirit of Polishness. Through subsequent orders, the occupying authorities sought to remove them from the city. The Polish City Council, headed by the commissary mayor Julian Kulski, took all measures to save these monuments. Most of the capital's monuments survived until the outbreak of the Warsaw Uprising, thanks to actions taken to save them. After 1944, only a few of them remained on the plinths.